STUDENTS’ ABILITY IN IDENTIFYING INTERROGATIVE SENTENCES THROUGH CONVERSATION TEXT - Sendy Fernando Saragi; Meysi Tamba; Yosa Delvina; Resperdiana Purba (elt, 2021)
ABSTRACT The research is entitled an analysis of student's ability in identifying interrogative sentences through conversation text in SMK PendidikanSiapMandiri. The purpose of the research is to analyze data in detail to see how far the students' understanding of using interrogative sentences in conversational texts was. In order, it will produce the right of fixed data. This method of research uses conversation text. By using qualitative data, collecting data in using a written test by doing two tests. The results showed that on the first test only a few students get a score of 75, it is estimated that only 30% of students got the score criteria. However, in the second test, the researcher gives another explanation to the students to better understand how to identify interrogative sentences. And the result is that the student's ability has increased by 50%, many students have successfully met the score criteria, namely at least 75. So, the result of the research shows that the analysis of students' ability in identifying interrogative sentences is still lacking. Therefore, the conclusion is they can improve their abilities even better by learning more about an interrogative sentence. Keywords: Conversation text, Interrogative Sentences, Writing.